A Survey of Wild Indigenous Cryptostylis ovata Orchid Populations in Western Australia Reveals Spillover of Exotic Viruses - Stephen Wylie; Hua Li; Shu Hui Koh (Viruses)
Cryptostylis ovata is a terrestrial orchid endemic to southwestern Australia. The virus status of C. ovata has not been studied. Eighty-three C. ovata samples from 16 populations were collected, and sequencing was used to identify RNA viruses from them. In one population, all tested plants were co-infected with isolates of the exotic-to-Australia viruses Ornithogalum mosaic virus (OrMV) and bean yellow mosaic virus (BYMV). In another population, one plant was infected with BYMV. No viruses were detected in the remaining populations. The OrMV isolate shared 98–99% nucleotide identity with isolates identified from wild indigenous Lachenalia (Iridaceae) plants in South Africa. This suggests that the source of OrMV in C. ovata may be one or more bulbous iridaceous flowering plants of southern African origin that were introduced to Western Australia as ornamentals and that have since become invasive weeds. One BYMV isolate from C. ovata also exhibited 99% nucleotide identity with strains isolated from the exotic leguminous crop Lupinus angustifolius in Western Australia, suggesting possible spillover to indigenous species from this source. This study with C. ovata highlights the probable role of invasive weeds and exotic crops as sources of exotic virus spillovers to indigenous plants.